Pendidikan Berbasis Islamic Worldview: Membangun Karakter dan Moral - Siroz, Anwar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate in more detail the integration of Islamic worldview values ​​in the educational curriculum and how it is essential to character and moral formation. With a deeper understanding of the relationship between Islamic worldview and character formation. It is hoped that this research can pave the way for improving Islamic education that is more holistic and relevant amidst the complexity of modern-day challenges. This research uses descriptive qualitative, a type of study that tries to describe things that are already happening, both artificial and natural. Where in this research there is an occurrence that must be developed in the character and moral aspects of students through Islamic WorldView-based education. The data source is obtained from the library (Library Research). the curriculum. The discovery of this ideology can be known by finding out the worldview contained in the curriculum, through the content of the lesson material to be conveyed. Islamic religious educators are figures who play a core role in passing on the intellectual tradition of the Islamic worldview to students at school. So it is concluded that education based on an Islamic worldview is to support the successful development of the persona and morals among pupils amidst the erosion of the morals of the country's youth by the massive current of globalization.